Photo-switching and -cyclisation of hydrogen bonded liquid crystals based on resveratrol. Issue 7 (2nd January 2020) - Blanke, Meik; Balszuweit, Jan; Saccone, Marco; Wölper, Christoph; Doblas Jiménez, David; Mezger, Markus; Voskuhl, Jens; Giese, Michael
Abstract : A series of hydrogen-bonded liquid crystals based on resveratrol and resveratrone is reported and investigated with respect to their photo-switchability (at 405 nm) and photo-cyclisation (at 300 nm). Abstract : A series of hydrogen-bonded liquid crystals based on resveratrol and resveratrone is reported and investigated with respect to their photo-switchability (at 405 nm) and photo-cyclisation (at 300 nm).